2022
DOI: 10.1371/journal.pone.0267092
|View full text |Cite
|
Sign up to set email alerts
|

Salivary inflammatory mediators as biomarkers for oral mucositis and oral mucosal dryness in cancer patients: A pilot study

Abstract: Oral mucositis (OM) is a common side effect in patients with cancer receiving chemotherapy and radiotherapy; however, no salivary mediator is known to be associated with OM. We aimed to determine candidate salivary inflammatory mediators potentially associated with OM in patients with cancer. To this end, we compared the relationships between OM grade, oral mucosal dryness, and inflammatory mediators (Interleukin (IL)-1β, IL-6, IL-10, IL-12p70, tumor necrosis factor (TNF), prostaglandin E2, and vascular endoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
0
0
1
Order By: Relevance
“…The proteomic approach for OM research has focused on biomarker development, particularly on inflammatory proteins observed after treatment-induced OM. Kiyomi et al [36] utilized a bead array and an enzyme-linked immunosorbent assay (ELISA) to identify potential biomarkers of OM from saliva or oral swab samples were taken from 20 leukemia or head and neck cancer patients undergoing treatment. Their study suggests that salivary IL-6, IL-10, and TNF-α may serve as predictors of OM occurrence and grade.…”
Section: Transcriptomics and Proteomicsmentioning
confidence: 99%
“…The proteomic approach for OM research has focused on biomarker development, particularly on inflammatory proteins observed after treatment-induced OM. Kiyomi et al [36] utilized a bead array and an enzyme-linked immunosorbent assay (ELISA) to identify potential biomarkers of OM from saliva or oral swab samples were taken from 20 leukemia or head and neck cancer patients undergoing treatment. Their study suggests that salivary IL-6, IL-10, and TNF-α may serve as predictors of OM occurrence and grade.…”
Section: Transcriptomics and Proteomicsmentioning
confidence: 99%
“…Foram avaliadas também, as citocinas em sangue e saliva para correlacionar com a gravidade da mucosite oral, o sangue apresentou correlação forte da expressão de TNF-α (ρ=0.403; p=0,009) em T0; e correlação moderada de TNF-α (ρ=0. 38 .…”
unclassified